2019
DOI: 10.1590/1518-8345.2695.3106
|View full text |Cite
|
Sign up to set email alerts
|

Dry care versus chlorhexidine cord care for prevention of omphalitis. Systematic review with meta-analysis

Abstract: Objective:to compare the effect of dry care and the application of chlorhexidine to the umbilical cord of newborns at risk of developing omphalitis. Method:systematic review with meta-analysis. Clinical trials comparing dry care with the application of clorexidine to evaluate omphalitis were selected. Methodological quality was evaluated using the Consolidated Standards of Reporting Trials. Results:the joint analysis of the studies shows a significant decrease in the risk of omphalitis in the chlorhexidine gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 31 publications
0
4
0
1
Order By: Relevance
“…18 A systematic review with meta-analysis performed by Lopez-Medina and co-workers from 9 eligible studies (118,903 NB in total) showed 64.03% of omphalitis cases belonged to the dry cord care group. 19 This research concluded that in high NMR (>10 deaths per 1000 live births) countries, 4% chlorhexidine application significantly protect against omphalitis in home births with inappropriate hygienic conditions and reinforced its use in developing countries. Whereas, in countries with less NMR, two types of cord care did not reveal any difference in preventing omphalitis.…”
Section: Discussionmentioning
confidence: 95%
“…18 A systematic review with meta-analysis performed by Lopez-Medina and co-workers from 9 eligible studies (118,903 NB in total) showed 64.03% of omphalitis cases belonged to the dry cord care group. 19 This research concluded that in high NMR (>10 deaths per 1000 live births) countries, 4% chlorhexidine application significantly protect against omphalitis in home births with inappropriate hygienic conditions and reinforced its use in developing countries. Whereas, in countries with less NMR, two types of cord care did not reveal any difference in preventing omphalitis.…”
Section: Discussionmentioning
confidence: 95%
“…Significant evidence points out that the topical application of 10/15 4% chlorhexidine to the umbilical stump is the most indicated, given its impact in reducing infections, including omphalitis, and neonatal mortality. 6 However, in Brazilian territory, the recommended by the Ministry of Health (MoH) and the Brazilian Society of Pediatrics (SBP -Sociedade Brasileira de Pediatria), is that at the end of the bath, carried out with water and neutral soap, the stump must be dried and at its base apply 70% alcohol, and also to each diaper change, in order to speed up mummification and fall, this type of care being the most recurrent in the statements. However, 70% alcohol does not provide drying, has less antibacterial effect than other antimicrobials, delays the fall of the cord, in addition to causing cutaneous hemorrhagic necrosis and serum levels with toxicity, unlike chlorhexidine, which has systemic absorption without toxic effects.…”
Section: Discussionmentioning
confidence: 99%
“…4 Community care, such as exclusive breastfeeding and correct hygiene, including the umbilical stump, are preventive and basic practices that significantly contribute to reducing neonatal morbidity and mortality. [5][6] However, families have their own body of knowledge derived from previous experiences, which makes them hold unique knowledge built in life trajectories. 7 Therefore, in the postnatal period, erroneous care practices can be performed and/or new learning demands can emerge and affect newborns' health, directly or indirectly.…”
Section: Introductionmentioning
confidence: 99%
“…Durante o processo de mumificação, cuidados de higiene com o coto umbilical são essenciais na prevenção da onfalite (infecção bacteriana do coto umbilical), que apresenta incidência de 0,7% em países desenvolvidos e 2,7% em países em desenvolvimento (2) .…”
Section: Introductionunclassified